Perempuan, Media Digital, dan Penguatan Ekonomi di Masa Pandemi Covid 19 - Yulianti Yulianti; Andalusia Neneng Permatasari; Muthiah Umar; Dede Lilis Chaerowati (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The Covid 19 virus outbreak has affected all aspects of life without exception. The economic crisis is in sight and requires the cooperation of all parties, including women. There will be no sustainable empowerment without involving women. In line with this, the Bandung City Aisyiyah Organization appears as the vanguard to strengthen the women's economy. The approach used in this empowerment is Asset Based Community Development (ABCD). The focus of empowerment is focused on optimizing the potential for economic empowerment, especially for women in the city of Bandung. Training and assistance, starting from the importance of understanding the function of digital media for business development, creating content for networking and promotion, to the practice of using digital media optimally. The empowerment results show a significant increase in cognition in Aisyiyah women in Bandung. Empowerment like this should be made sustainable.